Microbiome Associated With Gambierdiscus balechii Cultures Under Different Toxicity Conditions - Wu, Zhen; Lee, Wai Hin; Liu, Zijian; Lin, Senjie; Lam, Paul K. S. (Frontiers in Marine Science, 2022)
Dinoflagellates, including harmful algal bloom species, are known to co-exist with and rely upon bacteria but how the microbiome changes with the physiologies of the cognate dinoflagellates is poorly understood. Here, we used 16S rRNA gene meta-barcoding to characterize the bacterial community in the cultures of Gambierdiscus balechii, a ciguatoxin-like-producing benthic dinoflagellate, under different nitrogen (N)-nutrient conditions and at different ciguatoxin-like-producing growth. The high-throughput sequencing of a total of 12 libraries generated 926,438 reads which were classified into 16 phyla. We observed a shift of the G. balechii-associated microbiome from N-replete to low-N conditions and from the early (low toxin) to the late exponential (high toxin) growth stage. Common across these conditions were species from families Rhodobacteraceae and Flavobacteriaceae. Species abundant in the low-N condition mainly included Planctomyces, Ekhidna, and Lactobacillus. Dominant or high abundant microbial taxa in the high toxin-producing stage (N-replete, late exponential stage) were Oceanococcus and Marinoscillum. Under this condition, one Rhizobiales bacterium, Oricola, also increased in relative abundance. Our study documents the high diversity and dynamics of the G. balechii-associated microbiome, and identifies condition-specific sub-communities: the core (constitutive) microbiome that stably co-exists with G. balechii, the bacterial lineages that are responsive to N-nutrient variations, and species whose abundances are correlated with toxin content of the dinoflagellate. These findings demonstrate that particular bacterial groups are responsive to N-nutrient or toxicity changes of G. balechii and thus will be useful for further investigations on the associated microbiome’s interactions with benthic dinoflagellates and functions in the course of benthic harmful algae blooms.